Load variations in high-performance netballers across seasons and competition levels. (4th July 2021) - Bardzinski, Tanisha; Dwyer, Dan; Young, Chris; Piromalli, Laura; Bruce, Lyndell
ABSTRACT: Internal loads as measured by session rating of perceived exertion (sRPE) of high-performance netballers were explored using data from athletes who competed in the 2017 and 2018 Suncorp Super Netball (SSN) and 2016 to 2018 Australian Netball League (ANL) competitions. Data were analysed to determine if there were differences between season phase (pre- and in-season), competition level, session type (combined training, court training, match, weights and conditioning) and year. Pre-season load (468.9 ± 183.2au) was higher than in-season load (431.3 ± 188.9au) ( p < .05, ƞρ 2  = .016). Load was higher in the 2017 season (466.0 ± 193.2au) than both the 2016 (442.4 ± 189.3au) and 2018 seasons (441.0 ± 179.3au) ( p < .05, ƞρ 2  = .005). Each session type was significantly different than the other apart from combined training and court training (combined training 546.5 ± 201.5au; court training 538.7 ± 172.7au; match 473.6 ± 164.5au; weights 400.1 ± 121.1au; conditioning 276.5 ± 121.8au) ( p < .05, ƞρ 2  = .25). There was a competition × season phase interaction ( p < .05, ƞρ 2  = .003) where ANL athletes had the highest pre-season load (472.6 ± 193.7au) but the lowest in-season load (415.2 ± 179.2au). These findings present a novel understanding of the loads experienced by high-performance netballers over multiple seasons.